Operation efficiency increasing of a logistic center - Karabylo, V.S. (ХНУ ім. В. Н. Каразіна, 2012)
The article considers the efficiency increasing of a logistic center operation and its disadvantages. Shown the analysis of theoretical foundations of the logistics centers’ operation
В статье рассматривается эффективность увеличения действия центра логистики и его недостатки. Показан анализ теоретического основания действий центров логистики.
Keywords: theoretical foundation; logistic center operation